The role of deposition temperature in the photovoltaic properties of rf-sputtered cdse thin films - Rosly H.N.; Rahman K.S.; Abdullah S.F.; Harif M.N.; Doroody C.; Chelvanathan P.; Misran H.; Sopian K.; Amin N. (MDPI AG, 2023)
Cadmium selenide (CdSe) thin films were grown on borosilicate glass substrates using the RF magnetron sputtering method. In this study, CdSe thin film was deposited at a deposition temperature in the range of 25?C to 400?C. The influence of deposition or growth temperature on the structural, morphological, and opto-electrical properties of CdSe films was investigated elaborately to achieve a good-quality window layer for solar-cell applications. The crystal structure, surface morphology, and opto-electrical characteristics of sputtered CdSe films were determined using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UVVis spectrophotometry, and Hall effect measurement, respectively. The XRD results revealed the polycrystalline nature of CdSe, with a hexagonal structure having a strong preferential orientation toward the (002) plane. As evident from the FESEM images, the average grain size and surface morphology of the films were dependent on deposition temperatures. The carrier concentration was obtained as 1014 cm?3. The band gap in the range of 1.651.79 eV was found. The explored results suggested that sputtered CdSe thin film deposited at 300?C has the potential to be used as a window layer in solar cells. 2021 by the authors. Licensee MDPI, Basel, Switzerland.